Participatory Design of an Electronic Medical Record for Paediatric Palliative Care: A Think-Aloud Study with Nurses and Physicians - Sven Kernebeck; Theresa Sophie Busse; Chantal Jux; Dorothee Meyer; Larissa Alice Dreier; Daniel Zenz; Boris Zernikow; Jan Peter Ehlers (MDPI AG, 2021)
Background: Electronic medical records (EMRs) offer a promising approach to mapping and documenting the complex information gathered in paediatric palliative care (PPC). However, if they are not well developed, poorly implemented EMRs have unintended consequences that may cause harm to patients. One approach to preventing such harm is the involvement of users in the participatory design to ensure user acceptance and patient safety. Therefore, the aim of this study is to evaluate the acceptance of a novel patient chart module (PCM) as part of an EMR from the perspective of potential users in PPC and to involve these professionals in the design process. Methods: A qualitative observational study with N = 16 PPC professionals (n = 10 nurses, n = 6 physicians) was conducted, including concurrent think aloud (CTA) and semi-structured interviews. A structured content analysis based on the Unified Theory of Acceptance and Use of Technology was applied. Results: The results can be summarized in terms of general observations, performance expectancy, effort expectancy and facilitating conditions, all of which are likely to have a positive influence on acceptance of the PCM from the user perspective in the context of PPC. Conclusions: The involvement of users in the development of EMRs is important for meeting the requirements in PPC. Further software adaptations are necessary to implement these requirements.